The effects of central bank independence and inflation targeting on macroeconomic performance: Evidence from natural experiments - Michael Parkin (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2013)
Does a central bank that is independent of political influence deliver a better macroeconomic performance than one that implements monetary policy decisions taken by government? Does an inflation targeting agreement between central bank and government improve macroeconomic performance? And does the combination of an independent central bank and inflation targeting deliver an even better performance than either on its own? This paper addresses these questions by examining the outcomes of some natural experiments. [...]
Keywords: 330